2017
DOI: 10.1155/2017/7232361
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Type III Interferons in Hepatitis C Virus Infection and Therapy

Abstract: The human interferon (IFN) response is a key innate immune mechanism to fight virus infection. IFNs are host-encoded secreted proteins, which induce IFN-stimulated genes (ISGs) with antiviral properties. Among the three classes of IFNs, type III IFNs, also called IFN lambdas (IFNLs), are an essential component of the innate immune response to hepatitis C virus (HCV). In particular, human polymorphisms in IFNL gene loci correlate with hepatitis C disease progression and with treatment response. To date, the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 138 publications
1
22
0
1
Order By: Relevance
“…Numerous reports indicated that the unfavorable IFNL3 and IFNL4 genotypes are associated with reduced response to pegIFN‐α/RBV therapy and augmented the frequency of HCV infection in PBMCs . The impact of IFNL3 rs12979860 genotypes on OCI is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports indicated that the unfavorable IFNL3 and IFNL4 genotypes are associated with reduced response to pegIFN‐α/RBV therapy and augmented the frequency of HCV infection in PBMCs . The impact of IFNL3 rs12979860 genotypes on OCI is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired ability of neonatal pDCs to initiate an adequate antiviral immune response upon TLR‐specific activation implies clinical and immunological relevance in this infection prone population. Indeed, IL‐29 seems to be a promising candidate for the treatment of acute and chronic viral infections such as hepatitis C or E . However, based on our data, therapeutic approaches targeting IL‐29 might display reduced efficacy in neonates.…”
Section: Discussionmentioning
confidence: 94%
“…As it comprises “cytokine‐mediated signalling pathway,” it mediates many cellular functions in HCV clearance. Interferon, lambda (IFNL) is promising cytokine‐based antiviral treatment with fewer side effect, and IFNL4 and IFNL3 polymorphisms were shown to be predictive of treatment response, further highlighting the significance of IFNL in HCV infection …”
Section: Discussionmentioning
confidence: 99%